Pembuatan Animasi Wallpaper 2D Dengan Aplikasi Adobe After Effect - Vernando, Veron; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2024)
In the world of animation, 2D animation is very popular among people from children to adults. Animation is a method that is widely used by editors or animators in the world of cinema today, either for a complete whole between parts of a film or integrated into a live film. The definition of animation also comes from the word 'to animate' which means to move and animate. For example, an object that should be dead is then moved with changes little by little so that it can give the object the impression of life. 2-Dimensional Animation is in the form of moving images that are formed from a collection of objects (2-dimensional images) that have been arranged in a regular manner by following a predetermined movement path at each time increment that occurs. In animation, there are several techniques that can be used to create 2D animation, including Cell Animation, Silhouette, Keyframe, Rotoscope and Stop Motion. Animation has become widely known since television media was able to present moving images. By animating in 2D, one of the Adobe applications is also used in 2D animation, namely Adobe After Effects. Adobe After Effects is used to broadcast television broadcasts and play films to support the necessary software, image editing and 3D animation. Ibis Paint X is an application used by smartphone users to animate 2D by drawing illustrations. Ibis Paint X is an application used for drawing and editing images with various editor features that can be used, such as drawing brushes, filters, fonts and other features that can make it easier for users to create images, even for beginners